Montgomery Blair Science, Mathematics and Computer Science Magnet Program: A Successful Model for Meeting the Needs of Highly Able STEM Learners. (October 2016) - Stein, David; Ostrander, Peter; Lee, G. Maie
The Magnet Program at Montgomery Blair High School is an application-based magnet program utilizing a curriculum focused on science, mathematics, and computer science catering to interested, talented, and eager to learn students in Montgomery County, Maryland. This article identifies and discusses some of the unique aspects of the Magnet Program that promote effective teaching and learning in a school-within-a-school magnet model. These signature qualities that make the Magnet Program a success align with the goal of providing a unique educational experience to highly able learners. The authors hope to provide insight into how effective magnet programs can support both the needs of their students and the larger school community.